The Neighbourhood and Linkages between Incarceration and Homelessness. State of the Art and Directions of Contemporary Research - Szczepanik, Renata (INSTED: Interdisciplinary Studies in Education & Society, 2023)
This paper presents a review of research findings on the nexus between incarceration and homelessness. The most important ways of explaining the connections between these two problems have been shown. The article also focuses on presenting the state of knowledge about the links between homelessness and incarceration in Poland. Existing gaps in this area have also been marked.